The Effect of Selective Thinking Strategy Supported by Hypermedia on Learning Some Basic Football Skills for Students - Khamees, Imad Mohsin (Indonesian Journal Publisher, 2025)
The aim of the research is to: design educational units according to the strategy of selective thinking supported by hypermedia and design educational units according to hypermedia and identify the effect of the strategy of selective thinking supported by hypermedia in developing the performance of the most important basic skills in football for students and identify the effect of hypermedia in developing the performance of the most important basic skills in football for students. And identify the significance of the differences between the three research groups (the control group and the two experimental groups) in the results of the post-tests. The researcher used the experimental method by designing equivalent groups, as shown in the experimental design of the research. The researcher used the experimental design with two experimental groups and one control group. The research community consisted of second-grade students at Tariq Bin Ziyad Intermediate School for Boys, Diyala Governorate Education Directorate, for the academic year 2024-2025, numbering (93) students, so that the number of sample members became (60) students, constituting a percentage of (64.51%) of the original community, who were randomly divided by lottery into three groups, a control group and two experimental groups, with (20) students for each group. The researcher then conducted equivalence and prepared learning units according to the first and second experimental groups. A post-test was then conducted, followed by a statistical kit. Conclusions were reached, the most important of which is that using a hypermedia-supported selective thinking strategy significantly improves students' performance in basic soccer skills, such as passing, dribbling, and scoring. One of the most important recommendations is the need to apply a hypermedia-supported selective thinking strategy to teaching other sports skills, not just soccer, to enhance learning effectiveness.